Influência da tetraciclina no desenvolvimento hepático e renal de filhotes de ratas - Machado, Ana Lourdes da Silva [UNESP] (2000)
This study aims to evaluate the possible effects of tetracycline administered to pregnant rats on kidney and liver development of their offspring. Fifteen rats were used - three controls and twelve treated ones. The control group received saline injections while the experimental groups were administered tetracycline chlorhidrate in the doses of 25, 50, 75 and 100mglkg, intraperitoneally, in a single injection, on the tenth day of pregnancy. The sucking were sacrificed at birth and after ten, twenty and thirty days of life. The liver specimes showed vacuolizations, necrosis, inflammation and sinusoidal dilatations, more evident in the newborn. Mitosis, early increase of Kupffer cells population and hypertrophy of hepatocytes with greater synthesis of glycogen were present in the 10th and twentieth days of life. The kidney specimens showed slight tubular vacuolizations and necrosis, more prominent in the newbom, as well as signs of tubular regeneration at the tenth and twentieth days. These results suggest that the organs studied went through several transitory morphological changes during development but presented signs of regeneration along the first days of life